Factors influencing meat emulsion properties and product texture: A review. Issue 10 (3rd July 2017) - Santhi, D.; Kalaikannan, A.; Sureshkumar, S.
Abstract: Emulsion-based meat products play an important role in modern meat industry. Though meat batters have been prepared traditionally since long back in the history, the scientific principles and the knowhow are significantly important in the case of commercial products. In India, the market for emulsion meat products is gaining importance in the recent years and the native producers are in critical need for the scientific basis of production of emulsion meat products with better yield, good sensory qualities and nutrition. Hence, this review will throw light on some of the important factors which influence the properties of meat emulsion such as stability, structure, etc. and the product texture and yield as the revealed by past researches which will be useful to the meat processors in their practical application in preparing meat emulsion products.